Islamic ethics and nutrigenomics: a methodological approach to constructing a theoretical framework - Muhammad Yusoff, Muhammad Fawwaz; Ab Razak, Nur Izah; Mohd@Amat, Robiatul Adawiyah (Transnational Press London, 2024)
Individualised nutrition based on knowledge of nutrigenomics is becoming a major scientific and health interest subject worldwide. Still, it adds a layer of complexity that may benefit and harm the social aspects of eating. In the case of advancing the knowledge of gene–nutrient interactions and other scientific disciplines, all religious communities of the world, including Muslims, have statements of principles that express the identity and commitment defining one community from others. To properly develop a religiously acceptable framework that encompasses important aspects of the Islamic tradition, indirect input from Islamic scientific philosophers, scholars, luminaries and source materials is required. Without trying to be thorough, this work addresses that need and provides new opportunities for future research and publishing in Islamic ethics, genome, and food (nature). It also analyses Muslim scholars’ arguments and deliberations on the ethical framework that extends beyond the binary dichotomy between right and wrong (al-ʾamr bi al-maʿrūf wa al-nahy ʿan al-munkar) in Islamic jurisprudence. This qualitative study utilised a range of Islamic intellectual voices to build a theoretical framework of Islamic ethics in nutrigenomics based on constructivist grounded theory as the broader research approach. Constant conversation between nutrigenomics (modern science) and Islamic ethics is suggested to help Muslims grasp this dialectic better. It is only by taking a more comprehensive view incorporating theological, spiritual, jurisprudential, and social dimensions that one can make a stronger case and construct a foundational theoretical framework to build applications of Islamic ethics in nutrigenomics. Likewise, a systematic approach to developing a framework anchored in these sources is required to properly place the area of Islamic ethics in nutrigenomics and pave the way for future research on indigenous intervention development.